UNLOCKING THE POTENTIAL OF BIOENERGY: A SUSTAINABLE SOLUTION FOR ENERGY SECURITY, WASTE MANAGEMENT, AND ENVIRONMENTAL CONSERVATION - Muhammad Bashir Kabir,; Isah, A.; Yabo, Amina Mahmud; Garba, Rukayya Abubakar; Umar, B. A. (FUDMA JOURNAL OF SCIENCES, 2024)
The study was carried out to generate biogas from fresh cowdung. Proximate analysis on the cow-dung sample revealed moisture content to be 60.53%, Ash content 11.01%, total solids 39.47%, volatile matter 10.78%, protein content 12%, nitrogen content 1.6%, carbohydrate 5.68% and fixed carbon 17.68%. The pH and Temperature were measured daily at 2:00pm, the temperature ranged from 30OC-38OC and the pH range was 6.7 - 7.2. The gas produced was measured daily by calculating the volume with the height increased daily up to 36 days. The results showed a typical biogas production curve, consisting of lag, acceleration, maturation, and decline phases. The optimal retention time for biogas production is identified as 20-30 days, during which biogas yields are highest. The findings indicate that microorganisms require an initial adaptation period (Days 1-3) before biogas production commences, followed by a significant increase in production (Days 11-20) and a stable production rate (Days 21-30). A decline in production is observed after 30 days. This study highlights the importance of retention time in biogas production and demonstrates the need for monitoring production kinetics to optimize retention time for specific substrates and microbial communities. The results have implications for the design and operation of biogas production systems.
Keywords: Cow-dung; Waste management; Bioenergy; Environmental conservation